Сonditions for the obtaining of tocopherols from deodorizing distillates of sunflower oil - Demydova, A. O.; Nosenko, T. T.; Shemanska, Evgeniya; Molchenko, S. M. (Національний університет харчових технологій, 2019)
Introduction. A deodorizer distillate is a byproduct of oil deodoration, a natural source of tocopherols. The methods of obtaining a native antioxidants from a sunflower deodorizer distillate was investigated in this study. Materials and methods. The sunflower deodorizer distillates from a local enterprise were used in this work. The unsaponificated fraction of deodorizer distillate was separated by saponification. The kinetics of sunflower oil oxidation with/without antioxidants is investigated by the volumetric method. Results and Discussion. Deodorizer distillate increased sunflower oil induction period of oxidation by 1.5 times. Antioxidant activity of obtained concentrates was proved by increase of the induction period of oil oxidation almost three times as result of them addition in the amount of 50 mg per 100 g. Thus, saponification of deodorizer distillate gives possibility to obtain sufficiently effective inhibitor of oxidation.
Keywords: tocopherol; deodorizer; distillate; antioxidant; oxidation; absoption